Analisis Unsur Intrinsik Pada Cerpen “Perempuan Terakhir” Karya M. Shoim Anwar dan Implementasi Pada Pembelajaran Bahasa Indonesia di SMA - Merdina Ziraluo; Helnanirma Susanti Fau; Agustinus Duha; Kalvintinus Ndruru; Anita Zagoto (Departement of Mathematics Education, 2024)
Literary works are human creations born with beautiful language and capable of evoking emotional responses in readers and listeners. Literary works such as short stories are miniatures of life with various issues. In short stories, a fragment of a character's life is narrated, filled with conflicts, touching or pleasant events, and leaving unforgettable impressions. In the short story of